2013
DOI: 10.1111/cpf.12031
|View full text |Cite
|
Sign up to set email alerts
|

Chronic nicotine effects on left ventricular function in healthy middle‐aged people: an echocardiographic study

Abstract: This study reveals that most systolic- and diastolic cardiac parameters are not chronically significantly altered in middle-aged long-term tobacco users compared with age-matched non-tobacco users.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…31 Acute nicotine exposure was also found to cause a significant decrease and delay in relaxation of both right and left ventricles. 32 Studies in healthy subjects have demonstrated acute impairment of LV diastolic function and inducement of a hyperdynamic RV in response to smoking a single cigarette. 33 Smoking is also a risk factor for coronary spasm both in the presence and absence of atherosclerotic coronary artery disease.…”
Section: Discussionmentioning
confidence: 99%
“…31 Acute nicotine exposure was also found to cause a significant decrease and delay in relaxation of both right and left ventricles. 32 Studies in healthy subjects have demonstrated acute impairment of LV diastolic function and inducement of a hyperdynamic RV in response to smoking a single cigarette. 33 Smoking is also a risk factor for coronary spasm both in the presence and absence of atherosclerotic coronary artery disease.…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, data on pulmonary function and comprehensive echocardiographic variables were absent. In another much smaller Swedish cohort study with 87 participants, neither heart rate nor ejection fraction could be shown to be influenced by smoking status . Therefore, we believe that this is the first large study reporting significant smoking‐related changes in CI.…”
Section: Discussionmentioning
confidence: 72%
“…Cardiac output indexed for body surface area (cardiac index, CI) is arguably one of the most relevant physiologic parameters of cardiac performance as it encompasses several of the aforementioned components. Previous studies have mainly focused on the acute effects of smoking on systolic and diastolic function, and only a few studies have evaluated the chronic effect of smoking status on echocardiographic variables. So, to date, smoking‐related effects on CI in otherwise healthy subjects are largely unexplored.…”
Section: Introductionmentioning
confidence: 99%